Nonhealing Ulcers with Rimming of the Adipose Tissues - Kittipong Wantavornprasert; Thiti Asawapanumas; Pravit Asawanonda (Karger Publishers, 2022)
Extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT) is a rare condition which has a very aggressive clinical outcome. The most common and typical presentation is the destructive tumor involving the nasal cavity or nasopharynx, referred to as lethal midline granuloma, while cutaneous involvement is found to be the second most involved site. In this report, we describe a case of an otherwise healthy 40-year-old female solely presenting with ulcerative plaques and subcutaneous nodules on her lower extremities. Although the rimming of adipocytes by atypical lymphocytes, which resembles subcutaneous panniculitis-like T-cell lymphoma, was found on histopathology, immunohistochemistry revealed the diagnosis of cutaneous ENKTCL-NT which portends a much worse prognosis. A positron emission tomography scan also detected a hypermetabolic mass on her nasal cavity despite negative findings on history and initial examination. After thorough investigation, her final diagnosis was ENKTCL-NT with extranasal involvement (cutaneous) stage IV.